Sibling Relationship Quality and Identity Formation: Testing of Gender Characteristics and Birth Order of Sibling as a Moderator - Michelle Caroline Gunawan; Darmawan Muttaqin (Journal of Educational, Health and Community Psychology, 2022)
Siblings play a significant role in the process of forming identity among adolescents. Therefore, this research examined the role of sibling characteristics such as gender and order of birth in moderating the quality of relations among siblings and adolescent identity formation. The respondents were adolescents aged 12-21 years, with at least one sibling having a maximum age gap of 4 years. The data collection technique used two measurement scales involving the warmth and closeness subscale in the Sibling Relationship Questionnaire and The Utrecht-Management of Identity Commitments Scale. Additionally, the hypothesis was tested using a tiered regression test. The analysis showed the role of same-gender characteristics and birth order strengthens the relationship between siblings with three aspects of identity formation, including commitment, in-depth exploration, and reconsideration of commitment. This finding indicates that adolescents having same-gender and older siblings have better relationship qualities that contribute to a more optimal identity formation.